Knowledge and Attitudes of Bar Attendants towards Second-Hand Smoke in Nyarugenge District, Rwanda - Furaha Mediatrice; Nicholas Ngomi; Erigene Rutayisire (Journal of Public Health International, 2020)
Report has shown that there is an increase of respiratory disease among bars attendants over time whereby in 2011, 32% of bars attendants reported respiratory diseases. The purpose of this study was to assess the knowledge and attitudes of bar attendants towards second-hand smoke (SHS) at work place in Nyarugenge District, Rwanda. This was a cross-sectional study using mixed methods of both qualitative and quantitative. A total of 384 bar attendants participated in the study. Quantitative data were analyzed using SPSS version 21 while qualitative data were analyzed using thematic analysis. Descriptive analysis using frequency and percentages was computed. he qualitative data was analyzed using thematic analysis. The majority of respondents (66.4%) were within the age group of 28-37 years, 60.2% of respondents were males, 60.9% of respondents were illiterate, and 57.3% of respondents were single at the time of data collection.The majority (78.6%) of the study respondents knew that Smoking is dangerous to human health. The cited consequences of SHS include air pollution that enter the respiratory system and damage the lungs, dizziness and others. All respondents agreed that people who smoke should not be allowed to smoke in public places. Improving bar attendants’ access to health education on SHS and encouraging continuous and constant exposure would significantly increase the knowledge and attitude levels of bar attendants towards SHS.
Keywords: Second hand smoke